2013
DOI: 10.2174/1567205011310040003
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Oxidative Stress in Older Patients with Mild Cognitive Impairment or Late Onset Alzheimer's Disease

Abstract: A large body of evidences obtained in human and animal brain tissue suggest a role of oxidative stress (OxS) in the pathogenesis of late onset Alzheimer's disease (LOAD); on the contrary, data on peripheral markers of OxS in LOAD are still controversial. We evaluated the serum levels of products of lipid peroxidation, hydroperoxides, advanced oxidation protein products, total and residual antioxidant power, thiols, and uric acid in a sample of 334 older individuals: 101 LOAD patients, 134 patients with mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 44 publications
2
68
1
1
Order By: Relevance
“…Even at the stage of MCI, damage inflicted by oxidative stress to key proteins leads to deficiencies in systems important to the brain, such as neurotransmitter release, cell signaling, energy metabolism, and the proteasome, which might lead to the progression and pathogenesis of cognitive decline (7). In addition, oxidative parameters in the circulation were also higher in patients from MCI groups than in the control group (23,24). In line with these findings, the levels of nitrotyrosine and 8-iso-PGF2a in this study showed a similar trend and were higher in elderly patients with type 2 diabetes with MCI than in those without MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Even at the stage of MCI, damage inflicted by oxidative stress to key proteins leads to deficiencies in systems important to the brain, such as neurotransmitter release, cell signaling, energy metabolism, and the proteasome, which might lead to the progression and pathogenesis of cognitive decline (7). In addition, oxidative parameters in the circulation were also higher in patients from MCI groups than in the control group (23,24). In line with these findings, the levels of nitrotyrosine and 8-iso-PGF2a in this study showed a similar trend and were higher in elderly patients with type 2 diabetes with MCI than in those without MCI.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to support an association between oxidative stress and neurodegenerative diseases [52], mild neurocognitive disorder [53], and neuropsychological disorders including depression/anxiety [54]. For example, Fig.…”
Section: Resolution Of Inflammation: Capitalizing On Nature's Defensementioning
confidence: 99%
“…Of the remaining 35 studies, 6 studies were excluded for irrelevant outcomes and 5 studies were excluded for no usable data. Thus, 24 studies were finally included into the meta-analysis [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35]. Among those 24 studies, 19 studies were published in English [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35] while the other 5 studies were published in Chinese [36][37][38][39][40]. Those 21 case-control studies included a total of 1128 cases of Alzheimer's disease and 2498 controls without Alzheimer's disease [14-24, 28-32, 36-40].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%